Analisis Kualitas Larutan Mol (Mikoorganisme Lokal) Berbasis Daun Gamal (Gliricidia Sepium) - SENI, IDA AYU YADNYA; ATMAJA, I WAYAN DANA; SUTARI, NI WAYAN SRI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
Normal 0 false false false EN-US X-NONE X-NONE ABSTRACT Quality Analysis of MOL (Local Microorganism) Solution Based on Gamal ( Gliricidia sepium ) Leaves The purpose of this research was to find out the effects of gamal ( Gliricidia sepium ) leaves concentration and term of fermentation to the quality of MOL (local microorganism) solution. The research was held on September 2012 until November 2012, at Soil Laboratory , Faculty of Agriculture, Udayana University. Randomizing block design with two factors, including gamal leaves concentration (K) and fermentation term (F). The observation parameters of this research were total population of bacteria, total population of fungi, N-total, C-organic, C/N ratio. The analysis of gamal leaves concentration and the fermentation term was highly significant (P<0,01) affect. The total high population of bacteria in the K 1 treatment be found the treatment F 3 , 4,30 x 10 8 cfu ml -1 , the total high population of bacteria in the K 2 treatment can be found in the F 3 treatment is 6,37 x 10 8 cfu ml -1 , the total high of population of bacteria in the K 3 treatment can be found in the F 3 treatment is 8,63 x 10 8 cfu ml -1 , the total population of bacteria in the K 4 can be found in the F 3 treatment is 9,07 x 10 8 cfu ml -1 . The total population of fungi in the K 1 treatment can be found in the F 3 is 8,23 x 10 5 cfu ml -1 , the total population of fungi in the K 2 treatment can be found in the F 3 is 8,27 x 10 5 cfu ml -1 , the total population of fungi in the K 3 treatment can be found in the F 3 is treatment is 8,67 x 10 5 cfu ml -1 , the total population of fungi in the K 4 treatment can be found F 3 treatment is 10,20 x 10 5 cfu ml -1 . Concentration of 600 g/l gamal leaves on three weeks of fermentation have the best quality of mol solution. Keywords : Local Microorganisms ( MOL), gamal leaves , fermentation term